« Cette fois, la ligne rouge a été franchie » Conflits et ruptures de la relation de service dans la domesticité élitaire - Alizée Delpierre (La Nouvelle Revue du Travail)
Analysis of domestic work relationships have tended to focus on the asymmetrical subordination mechanisms that exist between employers and employees. This article uses the example of full-time domestic workers serving very wealthy families to analyse these relationships, specifically by examining the moment they break up. Employees’ frequent resignations offer a great deal of information about the conflicts at play. In work situations often organised on an ultra vires basis, domestic work relationships tend to be rooted in moral foundations designed to justify employers’ domination of employees. The study indicates, however, that this domination is limited by power relationships, and that there is a "red line" which, when crossed, crystallises the nature of employees’ resistance to this type of situation.